The power of local culture in regional tourism capital development - Trisoko, Riyono Gede; Yanti, Risna; Andita, Rahma Putri (CV. Austronesia Akademika, 2024)
The successful development of tourist destinations plays a crucial role in fostering local economic growth. However, regions often replicate tourism models without accounting for their unique geography, culture, demography, and socio-economic characteristics, leading to ineffective and costly outcomes. This research aims to highlight the significance of local cultural strengths in creating sustainable tourism strategies tailored to specific regional contexts. The study employs a literature review and observational approach, coupled with surveys distributed to tourists, business operators, and travel agencies. Both quantitative and qualitative analyses were utilized to identify trends, behaviors, and perceptions related to tourism development. The findings reveal that local culture, as an intrinsic social capital, holds significant potential to attract visitors by offering authentic and unique experiences. Cultural elements such as traditions, arts, culinary heritage, and social practices create strong narratives that differentiate destinations and enhance tourist satisfaction. Moreover, understanding local psychographic and demographic factors is pivotal in positioning tourism products effectively. The research concludes that leveraging local culture not only preserves regional identity but also stimulates entrepreneurship and economic prosperity. Tourism strategies that integrate cultural heritage with innovative marketing approaches have the potential to create sustainable competitive advantages, encouraging repeat visits and fostering community involvement. This study underscores the importance of aligning tourism development with local cultural values to achieve harmonious growth, benefiting both tourists and host communities.